Coastal communities' interest in football - Sumarni Een (SHS Web of Conferences)
The purpose of this study was to determine the interest of coastal communities in football. The method used is quantitative descriptive research. The sampling technique used purposive sampling, namely the coastal community of Tanjungpinang city totaling 150 people. The questionnaire instrument was a data collection tool in this study. The data analysis technique used a percentage interpreted in a criteria table. The results showed that 69% of coastal communities in Tanjungpinang City had an interest in football with high criteria.